Universal generalization
Type | Rule of inference |
---|---|
Field | Predicate logic |
Statement | Suppose [math]\displaystyle{ P }[/math] is true of any arbitrarily selected [math]\displaystyle{ p }[/math], then [math]\displaystyle{ P }[/math] is true of everything. |
Transformation rules |
---|
Propositional calculus |
Rules of inference |
Rules of replacement |
Predicate logic |
In predicate logic, generalization (also universal generalization, universal introduction,[1][2][3] GEN, UG) is a valid inference rule. It states that if [math]\displaystyle{ \vdash \!P(x) }[/math] has been derived, then [math]\displaystyle{ \vdash \!\forall x \, P(x) }[/math] can be derived.
Generalization with hypotheses
The full generalization rule allows for hypotheses to the left of the turnstile, but with restrictions. Assume [math]\displaystyle{ \Gamma }[/math] is a set of formulas, [math]\displaystyle{ \varphi }[/math] a formula, and [math]\displaystyle{ \Gamma \vdash \varphi(y) }[/math] has been derived. The generalization rule states that [math]\displaystyle{ \Gamma \vdash \forall x \, \varphi(x) }[/math] can be derived if [math]\displaystyle{ y }[/math] is not mentioned in [math]\displaystyle{ \Gamma }[/math] and [math]\displaystyle{ x }[/math] does not occur in [math]\displaystyle{ \varphi }[/math].
These restrictions are necessary for soundness. Without the first restriction, one could conclude [math]\displaystyle{ \forall x P(x) }[/math] from the hypothesis [math]\displaystyle{ P(y) }[/math]. Without the second restriction, one could make the following deduction:
- [math]\displaystyle{ \exists z \, \exists w \, ( z \not = w) }[/math] (Hypothesis)
- [math]\displaystyle{ \exists w \, (y \not = w) }[/math] (Existential instantiation)
- [math]\displaystyle{ y \not = x }[/math] (Existential instantiation)
- [math]\displaystyle{ \forall x \, (x \not = x) }[/math] (Faulty universal generalization)
This purports to show that [math]\displaystyle{ \exists z \, \exists w \, ( z \not = w) \vdash \forall x \, (x \not = x), }[/math] which is an unsound deduction. Note that [math]\displaystyle{ \Gamma \vdash \forall y \, \varphi(y) }[/math] is permissible if [math]\displaystyle{ y }[/math] is not mentioned in [math]\displaystyle{ \Gamma }[/math] (the second restriction need not apply, as the semantic structure of [math]\displaystyle{ \varphi(y) }[/math] is not being changed by the substitution of any variables).
Example of a proof
Prove: [math]\displaystyle{ \forall x \, (P(x) \rightarrow Q(x)) \rightarrow (\forall x \, P(x) \rightarrow \forall x \, Q(x)) }[/math] is derivable from [math]\displaystyle{ \forall x \, (P(x) \rightarrow Q(x)) }[/math] and [math]\displaystyle{ \forall x \, P(x) }[/math].
Proof:
Step | Formula | Justification |
---|---|---|
1 | [math]\displaystyle{ \forall x \, (P(x) \rightarrow Q(x)) }[/math] | Hypothesis |
2 | [math]\displaystyle{ \forall x \, P(x) }[/math] | Hypothesis |
3 | [math]\displaystyle{ (\forall x \, (P(x) \rightarrow Q(x))) \rightarrow (P(y) \rightarrow Q(y)) }[/math] | Universal instantiation |
4 | [math]\displaystyle{ P(y) \rightarrow Q(y) }[/math] | From (1) and (3) by Modus ponens |
5 | [math]\displaystyle{ (\forall x \, P(x)) \rightarrow P(y) }[/math] | Universal instantiation |
6 | [math]\displaystyle{ P(y) \ }[/math] | From (2) and (5) by Modus ponens |
7 | [math]\displaystyle{ Q(y) \ }[/math] | From (6) and (4) by Modus ponens |
8 | [math]\displaystyle{ \forall x \, Q(x) }[/math] | From (7) by Generalization |
9 | [math]\displaystyle{ \forall x \, (P(x) \rightarrow Q(x)), \forall x \, P(x) \vdash \forall x \, Q(x) }[/math] | Summary of (1) through (8) |
10 | [math]\displaystyle{ \forall x \, (P(x) \rightarrow Q(x)) \vdash \forall x \, P(x) \rightarrow \forall x \, Q(x) }[/math] | From (9) by Deduction theorem |
11 | [math]\displaystyle{ \vdash \forall x \, (P(x) \rightarrow Q(x)) \rightarrow (\forall x \, P(x) \rightarrow \forall x \, Q(x)) }[/math] | From (10) by Deduction theorem |
In this proof, universal generalization was used in step 8. The deduction theorem was applicable in steps 10 and 11 because the formulas being moved have no free variables.
See also
- First-order logic
- Hasty generalization
- Universal instantiation
References
Original source: https://en.wikipedia.org/wiki/Universal generalization.
Read more |